PENYUSUNAN DATA BLT DESA/KELURAHAN KECAMATAN NAINGGOLAN DALAM PENGELOLAAN INFORMASI BANTUAN SOSIAL - Jhon B.J. Situmorang; Martin Luter Purba (DEVELOPMENT: Journal of Community Engagement, 2025)
This study examines the compilation of village-level Direct Cash Assistance (BLT) data as an efficiency measure in managing social assistance information in Nainggolan Sub-district. The topic was chosen due to problems of inconsistent data formats and incomplete recipient identities, which complicate administrative processes. The method applied is descriptive qualitative, utilizing physical documents as secondary administrative data that were reorganized, validated, merged, and standardized using Microsoft Excel. The findings indicate that BLT data can be organized more neatly, documented, and consistent, while also providing an overview of variations in compliance among villages. In conclusion, BLT data compilation is a strategic step to improve efficiency in information social assistance management, and opens opportunities for digital governance development at the village level.